2020
DOI: 10.3390/su12041551
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Spillover Effect in Hi-Tech Industries: Empirical Evidence from China

Abstract: With ever-increasing economic globalization and rapid advancement of science and technology, developing high-tech industries have become an important way for many countries to achieve sustainable and environmentally friendly economic development. In this article, we aim to empirically test the critical factors, which can influence the spatial spillover of a country's high-tech industries. Using data from the high-tech industries in China during the years of 2007-2016, we establish a space lag model and a space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…However, such studies primarily utilize quantitative indicators of innovation, which may underestimate the gaps in regional innovation due to the underlying assumption of technological homogeneity in the innovative outputs. Other studies have drawn similar conclusions when utilizing data for R&D expenditure, human capital, government support, technology conversion expenditure, and other factors as proxies for the innovation in a region [8,[16][17][18]. However, such proxies may not properly represent innovation, as it should be the result of the transformation of these inputs [19], which may lead to bias in analyzing the spatial distribution of regional innovation.…”
Section: Introductionmentioning
confidence: 70%
“…However, such studies primarily utilize quantitative indicators of innovation, which may underestimate the gaps in regional innovation due to the underlying assumption of technological homogeneity in the innovative outputs. Other studies have drawn similar conclusions when utilizing data for R&D expenditure, human capital, government support, technology conversion expenditure, and other factors as proxies for the innovation in a region [8,[16][17][18]. However, such proxies may not properly represent innovation, as it should be the result of the transformation of these inputs [19], which may lead to bias in analyzing the spatial distribution of regional innovation.…”
Section: Introductionmentioning
confidence: 70%
“…The indirect effect is negative and significant at the 5% level, and the UTT of neighboring provinces decreases by 0.425 as industrial development increases by 1 unit, indicating that the level of industrial development harms the UTT of neighboring provinces. A possible reason is that industrial gatherings have a negative spatial spillover effect on the industrial development and technological innovation of neighboring regions [ 65 ], thereby suppressing the UTT level.…”
Section: Spatial Econometric Analysis Of Influencing Factorsmentioning
confidence: 99%
“…Lei and Li (2020) found that optimizing the business environment can stimulate the innovation energy of enterprises. Chen et al (2020) With the development of the new economic growth theory, some scholars, when exploring the influencing factors of technological progress, have found that the technological progress of a certain region not only depends on the innovation inputs of the region but also benefits from the innovation inputs of other regions, indicating that the innovation inputs have a spillover effect (Zhu et al, 2016). However, existing literature mostly ignores the spatial dependence between research objects when studying the innovation behavior characteristics of enterprises with different ownership.…”
Section: Introductionmentioning
confidence: 99%
“…Lei and Li (2020) found that optimizing the business environment can stimulate the innovation energy of enterprises. Chen et al (2020) investigated the spatial and temporal factors affecting the innovation output of high‐tech industries by establishing a spatial lag model with spatio‐temporal double mixed effects.…”
Section: Introductionmentioning
confidence: 99%